Answer:
(x, y) = (10, 5)
Explanation:
We notice that the y-coefficient is the same in both equations, and that the x-coefficient is smaller in the first equation. Subtracting one equation from the other will eliminate the y-variable. Subtracting the first equation from the second will result in a positive coefficient for x.
Subtracting the first equation from the second, we have ...
(-2x +2y) -(-4x +2y) = (-10) -(-30)
2x = 20 . . . .simplify
x = 10 . . . . . divide by 2
Substituting for x in the second equation gives ...
-2(10) +2y = -10
2y = 10 . . . . add 20
y = 5 . . . . . . divide by 2
The solution is (x, y) = (10, 5).